THE EFFECT OF PROBLEM-BASED LEARNING MODEL INTEGRATED WITH THE PEARSON ENGLISH PORTAL ON STUDENTS GRAMMAR MASTERY - Cesilia, Cesilia; Sihite, Meida Rabia; Zulkarnain, Iskandar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigated the effectiveness of integrating Problem-Based Learning (PBL) with the Pearson English Portal (PEP) to improve grammar proficiency among language learners. This study aims to fill in the gaps in the literature by examining the combined impact of this innovative pedagogical approach on the mastery of grammar skills. This study determined whether learners who engaged in PBL activities with PEP resources achieved a more significant increase in grammar proficiency than traditional instruction methods. Based on the independent t-test, the test value of the sig post (2-tailed) for the control class was 0.991 and for the experimental class was 0.991. Thus, the results of the independent t-test for hypothesis testing had a significant effect on the grammar mastery of students who learned using Problem-Based Learning Integrated with Pearson English Portal.